Elevated B-Type Natriuretic Peptide Level Expression Associated With Acute Myocardial Infarction Patients In Jammu Population (India) (Applied Biological Research, 2023)
B-type natriuretic peptide (BNP) is a highly sensitive and specific indicator of  the size of myocardial infarction, which can help in assessing the degree of  cardiovascular risk. Elevated BNP levels in patients hospitalized for acute  myocardial infarction (AMI) are associated with heart failure and mortality, and  the measurements of BNP in a short-term period could be helpful to predict the  future events. The role of short-term follow-up BNP level has not been  established in the patients with AMI. This retrospective study was conducted on  the patients admitted to the Government Medical College, Jammu (India). The  analysis of blood EDTA sample was analysed for BNP and this test was  performed by using a fully automated random access immunoassay analyser  whose principle is based on micro-particle enzyme immunoassay (MEIA). The  reference range of BNP is 0-100 pg mL-1. The study revealed a 90% BNP  increase in AMI patients in comparison to the 10% increase in normal healthy  ones. However, BNP showed elevated levels in healthy individuals suffering from  renal insufficiency. The BNP was > 100 pg mL-1in the majority of AMI patients  while in controls BNP is
Keywords: Acute myocardial infarction; B-type natriuretic peptide; enzyme immunoassay